Effects of whole-body electromyostimulation training in elderly people with sarcopenic obesity and sarcopenia: A literature review (Research, Society and Development, 2023)
This research had as its main objective to analyze the intervention of whole-body electrostimulation (WB-EMS) in the elderly population with sarcopenic obesity or sarcopenia. The methodology adopted was a systematic and exploratory literature review. We analyzed 11 articles published from 2013 to 2023, all selected from data from PubMed, Brazilian Journal of Development, Age and Aging and Clinical Interventions in Aging resulting from the descriptors: Elderly, Obesity, Sarcopenia, Strength Training, Health. We analyzed articles focused on randomized clinical trials. Among the main results found, it was possible to observe that whole body electrostimulation is one of the most recent methods and little known and used for the treatment of sarcopenic obesity and sarcopenia, however other methods such as strength training, whole body vibration training and HIIT, for example, would also be very effective for the treatment and maintenance of geriatric health. Therefore, being an innovative, fast and more comfortable modality for the elderly, whole body electrostimulation could easily be adopted as the main treatment. However, a low number of researches focused on the use of electrostimulation in the treatment of sarcopenic obesity and sarcopenia were identified.